(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
The article discusses the international experience of combating corruption in the public procurement system. Particular attention is paid to institutional, legal and digital mechanisms for reducing corruption risks. The practices of developed countries and international organizations are analyzed, and key tools for ensuring transparency and accountability of procurement procedures are identified.